THE STUDENTS MOTIVATION TOWARD PHYSICAL AND HEALTH EDUCATION SUBJECT (A GENERAL COURSE) IN STATE UNIVERSITY OF PADANG (UNP) - Firdaus, Kamal (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
The problems of the research were the students who frequently came late to their class and were unserious in the learning process. This research sought to reveal the students motivation toward Physical and Health Education subject in State university of Padang. This research was conducted in December. The number of the sample involved was 134 students. The data were analyzed by using percentage formula. Based on the results of the research, it was found out that the students intrinsic motivation toward Physical and Health Education subject is in average category while their extrinsic motivation toward Physical and Health Education subject is in good category. The students motivation in general toward Physical and Health Education subject in State University of Padang is in average category.